2018
DOI: 10.2196/jmir.8102
|View full text |Cite
|
Sign up to set email alerts
|

The Optimization of an eHealth Solution (Thought Spot) with Transition-Aged Youth in Postsecondary Settings: Participatory Design Research

Abstract: BackgroundSeventy percent of lifetime cases of mental illness emerge before the age of 24 years, but many youth are unable to access the support and services they require in a timely and appropriate way. With most youth using the internet, electronic health (eHealth) interventions are promising tools for reaching this population. Through participatory design research (PDR) engagement methods, Thought Spot, a Web- and mobile-based platform, was redeveloped to facilitate access to mental health services by trans… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 21 publications
0
40
0
Order By: Relevance
“…Given the many barriers that make meaningful youth engagement a challenge [ 56 ], obtaining 1291 individual responses during our recruitment is notable in its magnitude, especially given the short time frame (relative to other mental health trials). The high level of engagement in the study suggests that our commitment to co-creating solutions resonates with the postsecondary student population [ 28 ]. It may also reflect students’ enthusiasm for mental health solutions and mHealth-related research, suggesting a need for continued engagement with this population at a time when mental health concerns and suicide rates among youth continue to rise at postsecondary institutions [ 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the many barriers that make meaningful youth engagement a challenge [ 56 ], obtaining 1291 individual responses during our recruitment is notable in its magnitude, especially given the short time frame (relative to other mental health trials). The high level of engagement in the study suggests that our commitment to co-creating solutions resonates with the postsecondary student population [ 28 ]. It may also reflect students’ enthusiasm for mental health solutions and mHealth-related research, suggesting a need for continued engagement with this population at a time when mental health concerns and suicide rates among youth continue to rise at postsecondary institutions [ 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Participants were recruited using the most effective methods identified by two focus groups and the Thought Spot youth advisory committee during earlier stages of the project [ 28 ]. Participants were recruited through institutional and student-related listservs, bulletin boards, websites, social media, and class presentations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although our findings suggest that most papers have been published within the last 6 years, it is possible that we might have missed papers outside of this window in our search strategy. In addition, due to our scope of work on Thought Spot [ 26 , 27 , 29 ], our search was limited to examining interventions designed exclusively for transition-aged youth. Because we excluded papers evaluating interventions for other populations (eg, adults) and disease sites (eg, cardiology), there may have been evidence and guidance on the use of analytics in other areas of health care [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is also a lack of shared decision making across different countries [13] that further hampers the development of such models. In other geographical regions such as in Canada, others have shown that engagement methods using digital approaches i.e., 'Thought Spot', a web-based platform that aims to facilitate transition in youth, can be useful for those in post-secondary settings wishing to access mental health services [14]. More recently, another study is tracking experiences of young people in CAMHS as they transition through the CAMHS/AMHS boundary [15].…”
Section: Introductionmentioning
confidence: 99%